Disc1 Carrier Mice Exhibit Alterations in Neural pIGF-1Rβ and Related Kinase Expression - Sultana, Razia; Shrestha, Amita; Lee, Charles C.; Ogundele, Olalekan M. (Frontiers in Cellular Neuroscience, 2020)
Mutation of the disc1 gene underlies a broad range of developmental neuropsychiatric defects, including schizophrenia, depression, and bipolar disorder. The pathophysiological phenotypes linked with disc1 mutation are due to the truncation of the DISC1 primary protein structure. This leads to a defective post-synaptic scaffolding and kinase – GSK3 and Erk1/2 – signaling. As a result, synaptic function and maintenance are significantly impaired in the disc1 mutant brain. Among several other pathways, GSK3 and Erk1/2 are involved in insulin-like growth factor 1 receptor (IGF-1R) kinase signaling. Although disc1 mutation alters these kinases, it is unclear if the mutation impacts IGF-1R expression and activity in the brain. Here, we demonstrate that the expression of active IGF-1R (pIGF-1R) is altered in the hippocampus and prefrontal cortex of disc1 mutant mice and vary with the dose of the mutation (homozygous and heterozygous). The expression of pIGF-1Rβ decreased significantly in 129S (hom, disc1-/-) brains. In contrast, the 129S:B6 (het, disc1+/-) brains were characterized by an increase in pIGF-1R when compared with the C57BL/6 (control) level. The decrease in pIGF-1R level for the 129S brains was accompanied by the loss of Akt activity (S473 pAkt) and decreased Ser9 phosphorylation of GSK3 (increased basal GSK3β). Additionally, hippocampal and cortical pErk1/2 activity increased in the 129S hippocampus and cortex. Although 129S:B6 recorded alterations in pIGF-1Rβ-pAkt-GSK3β (like 129S, disc1+/+), there was no observable phenotypic change in pErk1/2 activity for the heterozygote (disc1+/-) mutant. In addition to GSK3β inhibition, we conclude that pIGF-1R, pAkt, and pErk1/2 are potential targets in disc1-/- (hom) mutant brain. On the other hand, pIGF-1R and pAkt can be further explored in disc1+/- (het) brain.